Mercury or Mercury Free Restorations in Oral Cavity - Rakesh Kumar Yadav; Umesh Pratap Verma; Rini Tiwari; Akhilanand Chaurasia (International Journal of Public Health Science (IJPHS), 2018)
Amalgam is basically a concoction of metals that has been used as a potent filling material in dentistry for the last 150 years. Amalgam usually consists of silver, mercury, tin and copper. Dental amalgam is a material used to fill cavities of tooth. Over the years, amalgam has become a topic of concern because it contains mercury. Mercury is a naturally occurring metal in the environment. Mercury exists as a liquid in room temperature but when heated, it becomes a gas. Flexibility of amalgam as a filling material is due Mercury. An alloy powder, a compound that is soft in nature when mixed with mercury makes it enough to mix and condense into the tooth. It hardens quickly and offers strong resistance to the forces of biting and chewing. There are studies reported on the safety of amalgam fillings. In 2005, European Union launched a comprehensive mercury strategy to reduce use of mercury. In 2008, countries like Norway and Denmark restricted the use of dental amalgam containing mercury. In 2009, this research was evaluated by U.S. Food and Drug Administration (FDA) and found no rationale to limit the use of amalgam.  There are certain restorative materials that are available commercially that are mercury free in nature like Gold, Porcelain, Gallium alloys, Composite resin restoratives etc. They offer many advantages over amalgams containing mercury like: seals the dentin from future decay, reinforces remaining tooth structure, provides smooth and bonded margins, conservative and it blends naturally.